A method for preparing low-hydroxyl, low-alkali metal high-purity quartz sand
Through the crushing sand making, flotation, oxidative pickling, calcining and composite acid solution pickling steps of igneous genus quartz, the complex problem of high-purity quartz sand in the existing technology depends on import and purification processes, the preparation of low-hydroxyl and low alkali metal high-purity quartz sand is achieved, and the needs of semiconductor quartz glass and photovoltaic quartz crucibles are met.
Patent Information
- Application Number
- CN202411505101.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-10-28
AI Technical Summary
In the prior art, high-purity quartz sand for semiconductor quartz glass and photovoltaic quartz crucibles mainly relies on imports, and the purification process is complex, making it difficult to meet domestic demand.
Using igneous genus quartz as raw material, low-hydroxyl, low-alkali metal high-purity quartz sand is prepared through crushing and sand making, flotation, oxidative pickling, calcining and composite acid solution pickling.
The preparation of low-hydroxyl and low-alkali metal high-purity quartz sand has been achieved, and the metal impurity content and hydroxyl content meet the standards of semiconductor quartz glass and photovoltaic quartz crucibles, reducing the dependence on imported raw materials.
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing low-hydroxyl and low-alkali metal high-purity quartz sand, belonging to the technical field of deep processing of non-metallic minerals. Background Art
[0002] The national standard GB / T32649-2016 "High-purity Quartz Sand for Photovoltaics" stipulates that high-purity quartz sand products for photovoltaics are used for quartz products such as diffusion tubes, carriers and arc crucibles used in the production of polycrystalline silicon and monocrystalline silicon photovoltaics; its technical requirements stipulate that the appearance of high-purity quartz sand for photovoltaics should be white particles with a certain degree of transparency, without any other color. The cumulative mass fraction of particles with a particle size of 70um-350um should be greater than or equal to 90%; the cumulative mass fraction of particles with a particle size less than 100um or greater than 300um should be less than 1%; the silicon dioxide content should be greater than or equal to 99.99%, and the loss on ignition should be less than or equal to 0.01%; the total content of impurity elements should be less than or equal to 25ug / g, of which the total content of potassium, lithium and sodium is less than 2.5ug / g. The specific standards are: Al<20ug< / g; Ca<1ug / g; Fe<0.5ug / g; Na<1ug / g; K<1ug / g; Li<1ug / g; Mg<0.5ug / g; Cr<0.1ug / g; Ni<0.1ug / g; B<0.1ug / g; Mn<0.2ug / g; Cu<0.1ug / g; Ti<1.5ug / g. High-purity quartz sand is mostly prepared from high-purity vein quartz or high-purity quartzite as raw materials. The reason is that the SiO2 contained in high-purity vein quartz and high-purity quartzite is of high purity and few impurities, which greatly reduces the difficulty of impurity removal during the purification process.
[0003] At present, high-purity quartz sand for semiconductor quartz glass and high-purity quartz sand for photovoltaic quartz crucibles mainly rely on imports. In addition to raw material factors, it is also closely related to the purification process. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing low-hydroxyl and low-alkali metal high-purity quartz sand by using igneous rock vein quartz as raw material.
[0005] The solution adopted by the present invention to solve the above technical problems is:
[0006] A method for preparing low-hydroxyl, low-alkali metal high-purity quartz sand comprises the following steps:
[0007] (1) Using igneous rock vein quartz as raw material, crushing the raw material to make sand, and obtaining raw quartz sand;
[0008] (2) HF is used as a pH adjuster and activator, and dodecylamine is used as a collector to float the raw quartz sand. In the flotation step, aluminosilicate impurities such as feldspar and other organic impurities are floated out with the foam, and the remaining is quartz sand.
[0009] (3) Using a composite acid solution composed of HF and ferrate to perform oxidative pickling and impurity removal on the quartz sand raw material after flotation; the purpose of this step is to remove the remaining aluminum silicate mineral impurities and sulfide mineral impurities in the quartz sand;
[0010] (4) After the quartz raw material is cleaned by oxidative pickling and mixed with carbon powder, it is calcined at 1100~1350℃ to remove gas-liquid inclusions in the quartz;
[0011] (5) The quartz raw material obtained in step (4) is pickled and impurities removed by using a composite acid solution composed of a halogen acid and a heavy metal complexing agent. The heavy metal complexing agent in the acid solution can form a complex with an alkali metal and an alkaline earth metal. After the pickling, the quartz raw material is washed with water and dried to obtain the low-hydroxyl, low-alkali metal high-purity quartz sand.
[0012] Furthermore, step (1) can select dry sand making or wet sand making, and after sand making, the material is classified, and raw materials with a particle size range of 50-150 mesh, 60-160 mesh, or 70-180 mesh are selected for subsequent processing.
[0013] Furthermore, an iron removal step is provided between step (1) and step (2), and the iron removal step adopts any one of electromagnetic separation and pickling or a combination of the two.
[0014] Furthermore, the acid solution used for pickling and iron removal is hydrochloric acid with a concentration of 28-30wt%, the pickling temperature is 80-85°C, and the pickling time is 3-4 hours.
[0015] Furthermore, in step (2), the flotation pH value range is 2.0-2.5; the collector concentration is 500-1000 g / t; and the number of flotation times is 2-8 times, preferably 3 times or more.
[0016] Furthermore, the Fe content in the quartz raw material obtained after flotation in step (2) is not higher than 0.008%, and the SiO2 content is not lower than 99%, which can be achieved by setting the number of flotation times.
[0017] Furthermore, in step (3), the temperature of the oxidative pickling and impurity removal is 80±5°C, and the pickling time is 2 to 4 hours; in step (5), the temperature of the pickling and impurity removal is 80±5°C, and the pickling time is 2 to 4 hours.
[0018] Furthermore, the pickling in step (3) and step (5) adopts fluidized pickling, such as the pickling equipment described in CN201110247061.4.
[0019] Furthermore, in the composite acid solution used for oxidative pickling and impurity removal in step (3), the mass fraction of HF is 10% to 30%, and the mass fraction of ferrate is 0.001% to 0.1%.
[0020] Furthermore, the ferrate is selected from sodium ferrate or potassium ferrate.
[0021] Furthermore, in step (5), the mass fraction of the halogen acid in the composite acid solution used for pickling and impurity removal is 20% to 30%, and the mass fraction of the heavy metal complexing agent is 0.01% to 0.2%, preferably 0.01% to 0.1%, and more preferably 0.04% to 0.05%.
[0022] Furthermore, the halogen acid is one of hydrochloric acid and HF or a mixture of the two.
[0023] Furthermore, the heavy metal complexing agent is selected from EDTA (ethylenediaminetetraacetic acid), DTPA (diethylenetriaminepentaacetic acid), EGTA (ethylene glycol bis(2-aminoethyl ether)tetraacetic acid), NTA (nitrilotriacetic acid); preferably EDTA and DTPA.
[0024] Furthermore, after the acid washing in step (3), the quartz raw material is deacidified, washed with tap water until neutral, and then dehydrated. In step (5), the quartz raw material is acid washed with a composite acid solution composed of a halogen acid and a heavy metal complexing agent, and then deacidified, washed with tap water until neutral, washed with electronic grade pure water at least three times, and then dehydrated and dried.
[0025] Furthermore, step (4) is performed before or after step (3). The oxidative pickling and degassing liquid inclusions can be interchangeably adjusted according to actual conditions during the actual production process, without any impact on the final quality of the product.
[0026] Furthermore, the calcination temperature in step (4) is preferably 1150° C. or above; when the calcination temperature in step (4) is 1200° C. or below, vacuum calcination is preferably used.
[0027] Furthermore, the calcination time in step (4) is 1 to 4 hours.
[0028] Furthermore, after the vacuum roasting in step (4) is completed, the material is cooled to a temperature no higher than the subsequent pickling temperature by no more than 25°C. For example, if the subsequent step is an oxidative pickling step, the pickling temperature is 80±5°C, and the material can be cooled to 95-105°C.
[0029] Furthermore, the mass of the wood carbon powder used in step (3) is 0.8% to 3% of the mass of the quartz raw material, and more preferably 1% to 2%.
[0030] Furthermore, the drying temperature in step (5) is 900-1000° C. to remove as much hydroxyl groups introduced during the washing process as possible.
[0031] The beneficial effects of the present invention are as follows:
[0032] The present invention takes domestic high-quality igneous rock vein quartz raw materials as the research object, and focuses on in-depth research on the purification process. Different from the process route commonly used in the prior art, which is to first calcine quartz ore, then water quench and sand making, the present invention first directly crushes the selected igneous rock vein quartz and makes sand, and then uses HF as a regulator and activator, and dodecylamine as a collector for flotation to remove aluminum silicate impurities such as feldspar, and then uses HF+ferrate for oxidative impurity removal to reduce the aluminum content and pyrite minerals to meet the requirements; then it is high-temperature roasted together with carbon powder to eliminate gas-liquid inclusions in quartz, that is, to reduce the hydroxyl content, and finally uses a composite acid solution composed of halogen acid solution and EDTA to pickle and remove impurities from quartz sand. The heavy metal complexing agent in the acid solution can form a complex with metals, especially alkali metals and alkaline earth metals, and is brought into the acid solution and removed by the acid solution without high-temperature chlorination treatment.
[0033] The quartz sand prepared by the preparation method of the present invention has a metal impurity content and a hydroxyl content that can reach the standards of high-purity quartz sand for semiconductor quartz glass and high-purity quartz sand for photovoltaic quartz crucibles. The hydroxyl content in quartz products such as quartz glass tubes and rods prepared using the sand as raw material can reach 5ppm or less. DETAILED DESCRIPTION
[0034] For a better understanding of the present invention, the following examples are provided to further illustrate the present invention, but the present invention is not limited to the following examples.
[0035] Example 1
[0036] Taking the igneous rock vein quartz ore in a certain place in Macheng as an example, the specific process of the present invention is explained;
[0037] 1. Material selection and sand making: The igneous rock vein quartz ore is selected, and then coarsely crushed by a jaw crusher, and finely crushed by a cone crusher to a particle size less than 15mm, and then sent to a rod mill for wet sand making. The mortar is first classified by a permanent magnetic separator with a magnetic field strength of 0.6T and then by a drum screen + hydraulic classifier. The 50-150 mesh mortar is collected and magnetically separated by an electromagnetic magnetic separator with a magnetic field strength of 1.8T, and then dehydrated for standby use.
[0038] 2. Pickling to remove iron: The quartz sand in step 1 is sent to a high-purity quartz sand pickling and purification device (see patent CN201110247061.4), and a hydrochloric acid solution with a mass percentage concentration of 28% is added. After countercurrent dynamic heating pickling at 80°C for 4 hours, the acid solution is removed, and then the quartz sand is washed with tap water until neutral and then dehydrated for use.
[0039] 3. Flotation to remove impurities: HF is used as an activator and pH adjuster, dodecylamine is used as a collector, pH is adjusted to 2.0, the dosage of dodecylamine is 500g / t, and flotation is performed twice. Feldspar and other aluminum silicate impurities and other organic impurities are floated out with the foam. After flotation, the quartz sand is dehydrated and set aside.
[0040] 4. Oxidative pickling: 20% HF + 0.01% sodium ferrate is used to form an oxidizing acid solution to perform countercurrent dynamic pickling and purification on the quartz sand in a high-purity quartz sand pickling and purification device. The acid solution temperature is maintained at 80°C and kept warm for 3 hours. The purpose is to use HF to remove the remaining aluminum silicate mineral impurities in the quartz sand, and to use the strong oxidizing property of sodium ferrate to oxidize and decompose the sulfide mineral impurities, so as to minimize the impurities in the quartz sand. After the insulation time is completed, the acid solution is removed, and the sand is washed with clean tap water until neutral, and then dehydrated for use.
[0041] 5. Inclusion removal: Mix the quartz sand in step 4 with 1.5% wood charcoal powder by mass, and put it into a high-temperature roasting furnace for vacuum roasting at 1200℃ for 120 minutes. During the high-temperature roasting process, the quartz particles undergo a crystal transformation, the silicon dioxide molecular bonds break and reconstruct, and the gas-liquid inclusions (structural water) in SiO2 will be effectively removed. After the roasting time is completed, cool to 95-105℃ and discharge the material for use.
[0042] 6. While hot, the quartz sand obtained in step 5 is sent into a composite acid solution composed of 20% HCl+5% HF+0.02% EDTA (all mass percentage concentrations), and is heated and dynamically pickled at a temperature of 80°C for 3 hours. Hydrochloric acid removes metal impurities, hydrofluoric acid removes aluminum silicate impurities, and EDTA forms a stable complex with alkali metal ions and alkaline earth metal ions in quartz and is brought into the acid solution. Then remove the acid solution. Wash the quartz sand with clean tap water until it is neutral, then wash it with electronic grade pure water at least three times and dehydrate it for standby use.
[0043] 7. High temperature drying: The quartz sand in step 6 is sent to a high temperature drying device for drying at 1000°C. The dried quartz sand is a high-purity quartz sand product with low hydroxyl and low alkali metal content.
[0044] Sampling was performed according to the standard of GB / T32649-2016 "High-purity quartz sand for photovoltaic use", and the impurity elements in the obtained quartz sand product were detected according to the impurity element detection method in "GB / T3284-2015 Quartz glass chemical composition analysis method", and the impurity elements in the obtained quartz sand product were detected according to "GB∕T 12442-2019 Test method for hydroxyl content in quartz glass". The sampling and testing methods of all embodiments of this application are the same, and the above standards are adopted.
[0045] The sum of the oxide contents of Al, Fe, K, Na, Ca, Mg, Li, Co, Ni, Cr, Mn, Ti, P, B and Cu in the quartz sand product obtained in this embodiment is 30 ppm; among them: Al: 13.8 ppm, Fe: 0.7 ppm, five alkali metal and alkaline earth metal impurities of K, Na, Ca, Mg and Li are all less than 1.0 ppm; titanium: 1.5 ppm.
[0046] The hydroxyl content in the quartz glass tube prepared from sand is 3 ppm.
[0047] Example 2
[0048] Taking the igneous rock vein quartz ore of Hong'an as an example, the specific process of the present invention is described:
[0049] 1. Material selection and sand making: The igneous rock vein quartz ore is selected, and then coarsely crushed by a jaw crusher, and finely crushed by a cone crusher to a particle size less than 15mm, and then sent to a rod mill for wet sand making. The mortar is first classified by a permanent magnetic separator with a magnetic field strength of 0.6T and then by a drum screen + hydraulic classifier. The 50-150 mesh mortar is collected and magnetically separated by an electromagnetic magnetic separator with a magnetic field strength of 1.8T, and then dehydrated for standby use.
[0050] 2. Pickling to remove iron: The quartz sand in step 1 is sent to a high-purity quartz sand pickling and purification device (see patent CN201110247061.4), and a hydrochloric acid solution with a mass percentage concentration of 28% is added. After countercurrent dynamic heating pickling at 80°C for 4 hours, the acid solution is removed, and then the quartz sand is washed with tap water until neutral and then dehydrated for use.
[0051] 3. Flotation to remove impurities: HF is used as an activator and pH adjuster, dodecylamine is used as a collector, pH is adjusted to 2.0, the dosage of dodecylamine is 500g / t, and flotation is performed twice. Feldspar and other aluminum silicate impurities and other organic impurities are floated out with the foam. After flotation, the quartz sand is dehydrated and set aside.
[0052] 4. Oxidative pickling: 25% HF + 0.02% sodium ferrate is used to form an oxidizing acid solution to perform countercurrent dynamic pickling and purification on the quartz sand in a high-purity quartz sand pickling and purification device. The acid solution temperature is maintained at 80°C and kept warm for 3 hours. The purpose is to use HF to remove the remaining aluminum silicate mineral impurities in the quartz sand, and to use the strong oxidizing property of sodium ferrate to oxidize and decompose the sulfide mineral impurities, so as to minimize the impurities in the quartz sand. After the insulation time is completed, the acid solution is removed, and the sand is washed with clean tap water until neutral, and then dehydrated for use.
[0053] 5. Inclusion removal: Mix the quartz sand in step 4 with 2.0% wood charcoal powder by mass, and send it into a high-temperature roasting furnace for vacuum roasting at 1200℃ for 60 minutes. During the high-temperature roasting process, the quartz particles undergo a crystal transformation, the silicon dioxide molecular bonds break and reconstruct, and the gas-liquid inclusions (structural water) in SiO2 will be effectively removed. After the roasting time is completed, cool to 95-105℃ and discharge the material for use.
[0054] 6. While hot, the quartz sand obtained in step 5 is sent into a composite acid solution composed of 20% HCl+8% HF+0.04% EDTA (all mass percentage concentrations), and is heated and dynamically pickled at a temperature of 80°C for 3 hours. Hydrochloric acid removes metal impurities, hydrofluoric acid removes aluminum silicate impurities, and EDTA forms a stable complex with alkali metal ions and alkaline earth metal ions in quartz and is brought into the acid solution. Then remove the acid solution. Wash the quartz sand with clean tap water until it is neutral, then wash it with electronic grade pure water at least three times and dehydrate it for standby use.
[0055] 7. High temperature drying: The quartz sand in step 6 is sent to a high temperature drying device for drying at 1000°C. The dried quartz sand is a high-purity quartz sand product with low hydroxyl and low alkali metal content.
[0056] Sampling and testing show that the sum of the oxide contents of Al, Fe, K, Na, Ca, Mg, Li, Co, Ni, Cr, Mn, Ti, P, B and Cu in the quartz sand product obtained in this embodiment is 28 ppm; among them: Al: 12.3 ppm, Fe: 0.6 ppm, the five alkali metal and alkaline earth metal impurities of K, Na, Ca, Mg and Li are all less than 1.0 ppm; titanium: 1.2 ppm.
[0057] The hydroxyl content in the quartz glass rod prepared using this sand as raw material is 2.16 ppm.
[0058] Example 3
[0059] Taking the igneous rock vein quartz ore in a certain place in Shaanxi as an example, the specific process of the present invention is explained:
[0060] 1. Material selection and sand making: The igneous rock vein quartz ore is selected, and then coarsely crushed by a jaw crusher, and finely crushed by a cone crusher to a particle size less than 15mm, and then sent to a rod mill for wet sand making. The mortar is first classified by a permanent magnetic separator with a magnetic field strength of 0.6T and then by a drum screen + hydraulic classifier. The 50-150 mesh mortar is collected and magnetically separated by an electromagnetic magnetic separator with a magnetic field strength of 1.8T, and then dehydrated for standby use.
[0061] 2. Pickling to remove iron: The quartz sand in step 1 is sent to a high-purity quartz sand pickling and purification device (see patent CN201110247061.4), and a hydrochloric acid solution with a mass percentage concentration of 28% is added. After countercurrent dynamic heating pickling at 80°C for 4 hours, the acid solution is removed, and then the quartz sand is washed with tap water until neutral and then dehydrated for use.
[0062] 3. Flotation to remove impurities: HF is used as an activator and pH adjuster, dodecylamine is used as a collector, pH is adjusted to 2.0, the dosage of dodecylamine is 500g / t, and flotation is performed twice. Feldspar and other aluminum silicate impurities and other organic impurities are floated out with the foam. After flotation, the quartz sand is dehydrated and set aside.
[0063] 4. Oxidative pickling: Use 30% HF + 0.03% sodium ferrate to form an oxidative acid solution, and perform countercurrent dynamic pickling and purification on the obtained quartz sand in a high-purity quartz sand pickling and purification device. Maintain the acid solution temperature at 80°C and keep it warm for 3 hours. After the insulation time is completed, remove the acid solution, wash it with clean tap water until it is neutral, and dehydrate it for use.
[0064] 5. Inclusion removal: Mix the quartz sand in step 4 with 1.0% wood carbon powder by mass and put it into a high-temperature roasting furnace for vacuum roasting at 1200℃ for 60 minutes. After the roasting time is completed, cool it to 95-105℃ and then discharge it for use.
[0065] 6. While hot, the quartz sand obtained in step 5 is sent into a composite acid solution composed of 20% HCl + 8% HF + 0.02% EDTA, and is subjected to dynamic pickling by heating at a pickling temperature of 80°C for 3 hours. The acid solution is then removed, and the quartz sand is washed with clean tap water until it is neutral, and then washed with electronic grade pure water for at least three times and then dehydrated for use.
[0066] 7. High temperature drying: The quartz sand in step 6 is sent to a high temperature drying device for drying at 1000°C. The dried quartz sand is a high-purity quartz sand product with low hydroxyl and low alkali metal content.
[0067] Sampling and testing show that the sum of the oxide contents of Al, Fe, K, Na, Ca, Mg, Li, Co, Ni, Cr, Mn, Ti, P, B and Cu in the quartz sand product obtained in this embodiment is 40 ppm; among them, Al: 15.3 ppm, Fe: 0.6 ppm, and the five alkali metal and alkaline earth metal impurities of K, Na, Ca, Mg and Li are all less than 1.0 ppm; titanium: 1.6 ppm.
[0068] The hydroxyl content in the quartz glass tube prepared using this sand as raw material is 4.8 ppm.
[0069] Example 4
[0070] This example uses the same igneous vein quartz ore and preparation method as Example 2, except that:
[0071] In step 7, the high temperature drying step, the drying temperature is 200°C.
[0072] The sum of the oxide contents of Al, Fe, K, Na, Ca, Mg, Li, Co, Ni, Cr, Mn, Ti, P, B and Cu in the obtained quartz sand product is 28 ppm; among them, Al: 15.1 ppm, Fe: 0.6 ppm, and the five alkali metal and alkaline earth metal impurities of K, Na, Ca, Mg and Li are all less than 1.0 ppm; titanium: 1.7 ppm.
[0073] The hydroxyl content in the quartz glass tube prepared using this sand as raw material is 2.8 ppm.
[0074] Example 5
[0075] Taking the igneous rock vein quartz ore in a certain place in Shaanxi as an example, the specific process of the present invention is explained:
[0076] 1. Material selection and sand making: The igneous rock vein quartz ore is selected, and then coarsely crushed by a jaw crusher, and finely crushed by a cone crusher to a particle size less than 15mm, and then sent to a rod mill for wet sand making. The mortar is first classified by a permanent magnetic separator with a magnetic field strength of 0.6T and then by a drum screen + hydraulic classifier. The 50-150 mesh mortar is collected and magnetically separated by an electromagnetic magnetic separator with a magnetic field strength of 1.8T, and then dehydrated for standby use.
[0077] 2. Pickling to remove iron: The quartz sand in step 1 is sent to a high-purity quartz sand pickling and purification device (see patent CN201110247061.4), and a hydrochloric acid solution with a mass percentage concentration of 28% is added. After countercurrent dynamic heating pickling at 80°C for 4 hours, the acid solution is removed, and then the quartz sand is washed with tap water until neutral and then dehydrated for use.
[0078] 3. Flotation to remove impurities: Use HF as activator and pH adjuster, dodecylamine as collector, adjust pH to 2.5, dodecylamine dosage is 800g / t, flotation is performed three times, and then the quartz sand is dehydrated for standby use.
[0079] 4. Oxidative pickling: Use 25% HF + 0.02% sodium ferrate to form an oxidative acid solution, and perform countercurrent dynamic pickling and purification on the obtained quartz sand in a high-purity quartz sand pickling and purification device. Maintain the acid solution temperature at 80°C and keep it warm for 3 hours. After the insulation time is completed, remove the acid solution, wash it with clean tap water until it is neutral, and dehydrate it for use.
[0080] 5. Inclusion removal: Mix the quartz sand in step 4 with 1.5% coke powder by mass and put it into a high-temperature roasting furnace for vacuum roasting at 1200℃ for 60 minutes. After the roasting time is completed, cool it to 95-105℃ and then discharge it for use.
[0081] 6. While hot, the quartz sand obtained in step 5 is sent into a composite acid solution composed of 25% HCl + 5% HF + 0.04% EDTA, and is subjected to dynamic pickling by heating at a pickling temperature of 80°C for 3 hours. The acid solution is then removed, and the quartz sand is washed with clean tap water until it is neutral, and then washed with electronic grade pure water for at least three times and then dehydrated for use.
[0082] 7. High temperature drying: The quartz sand in step 6 is sent to a high temperature drying device for drying at 950°C. The dried quartz sand is a high-purity quartz sand product with low hydroxyl and low alkali metal content.
[0083] Sampling and testing show that the sum of the oxide contents of Al, Fe, K, Na, Ca, Mg, Li, Co, Ni, Cr, Mn, Ti, P, B and Cu in the quartz sand product obtained in this embodiment is 25 ppm; among them, Al: 15.8 ppm, Fe: 0.5 ppm, and the five alkali metal and alkaline earth metal impurities of K, Na, Ca, Mg and Li are all less than 1.0 ppm; titanium: 1.4 ppm.
[0084] The hydroxyl content in the quartz glass rod prepared using this sand as raw material is 4.73 ppm.
[0085] Example 6
[0086] Taking the igneous rock vein quartz ore in a certain place in Inner Mongolia as an example, the specific process of the present invention is explained:
[0087] 1. Material selection and sand making: The igneous rock vein quartz ore is selected, and then coarsely crushed by a jaw crusher, and finely crushed by a cone crusher to a particle size less than 15mm, and then sent to a rod mill for wet sand making. The mortar is first classified by a permanent magnetic separator with a magnetic field strength of 0.6T and then by a drum screen + hydraulic classifier. The 50-150 mesh mortar is collected and magnetically separated by an electromagnetic magnetic separator with a magnetic field strength of 1.8T, and then dehydrated for standby use.
[0088] 2. Pickling to remove iron: The quartz sand in step 1 is sent to a high-purity quartz sand pickling and purification device (see patent CN201110247061.4), and a hydrochloric acid solution with a mass percentage concentration of 28% is added. After countercurrent dynamic heating pickling at 80°C for 4 hours, the acid solution is removed, and then the quartz sand is washed with tap water until neutral and then dehydrated for use.
[0089] 3. Flotation to remove impurities: Use HF as activator and pH adjuster, dodecylamine as collector, adjust pH to 2.5, dodecylamine dosage is 800g / t, flotation is performed three times, and then the quartz sand is dehydrated for standby use.
[0090] 4. Inclusion removal: Mix the quartz sand obtained in step 3 with 1.5% wood carbon powder by mass and put it into a high-temperature roasting furnace and roast it in vacuum at 1200℃ for 60 minutes. After the roasting time is completed, cool it to 95-105℃ and then discharge it for use.
[0091] 5. Oxidative pickling: While hot, the quartz material obtained in step 4 is sent into an oxidative acid solution composed of 25% HF + 0.02% sodium ferrate, and the quartz sand is heated and dynamically pickled and purified in a high-purity quartz sand pickling and purification device, and the acid solution temperature is maintained at 80°C and kept warm for 3 hours. After the insulation time is completed, the acid solution is removed, and the material is washed with clean tap water until neutral, and then dehydrated for use.
[0092] 6. Put the quartz sand in step 5 into the composite acid solution composed of 20% HCl + 8% HF + 0.04% EDTA (mass percentage concentration) for dynamic pickling at a temperature of 80°C for 3 hours, and then remove the acid solution. Wash the quartz sand with clean tap water until it is neutral, then wash it with electronic grade pure water for at least three times and dehydrate it for later use.
[0093] 7. High temperature drying: The quartz sand in step 6 is sent to a high temperature drying device for drying at 950°C. The dried quartz sand is a high-purity quartz sand product with low hydroxyl and low alkali metal content.
[0094] Sampling and testing show that the sum of the oxide contents of Al, Fe, K, Na, Ca, Mg, Li, Co, Ni, Cr, Mn, Ti, P, B and Cu in the quartz sand product obtained in this embodiment is 20.3 ppm; among them, Al: 13.6 ppm, Fe: 0.4 ppm, and the five alkali metal and alkaline earth metal impurities of K, Na, Ca, Mg and Li are all less than 1.0 ppm; titanium: 1.5 ppm.
[0095] The hydroxyl content in the quartz glass tube prepared using this sand as raw material is 3.44 ppm.
[0096] Example 7
[0097] Taking the igneous rock vein quartz ore in a certain place in Inner Mongolia as an example, the specific process of the present invention is described:
[0098] 1. Material selection and sand making: The igneous rock vein quartz ore is selected, and then coarsely crushed by a jaw crusher, and finely crushed by a cone crusher to a particle size less than 15mm, and then sent to a rod mill for wet sand making. The mortar is first classified by a permanent magnetic separator with a magnetic field strength of 0.6T and then by a drum screen + hydraulic classifier. The 50-150 mesh mortar is collected and magnetically separated by an electromagnetic magnetic separator with a magnetic field strength of 1.8T, and then dehydrated for standby use.
[0099] 2. Pickling to remove iron: The quartz sand in step 1 is sent to a high-purity quartz sand pickling and purification device (see patent CN201110247061.4), and a hydrochloric acid solution with a mass percentage concentration of 28% is added. After countercurrent dynamic heating pickling at 80°C for 4 hours, the acid solution is removed, and then the quartz sand is washed with tap water until neutral and then dehydrated for use.
[0100] 3. Flotation to remove impurities: Use HF as activator and pH adjuster, dodecylamine as collector, adjust pH to 2.5, dodecylamine dosage is 800g / t, flotation is performed three times, and then the quartz sand is dehydrated for standby use.
[0101] 4. Inclusion removal: Mix the quartz sand obtained in step 3 with 3.0% coke powder by mass and send it into a high-temperature roasting furnace and calcine it at 1200℃ for 60 minutes. After the roasting time is completed, cool it to 95-105℃ and then discharge it for use.
[0102] 5. Oxidative pickling: While hot, the quartz material obtained in step 4 is sent into an oxidative acid solution composed of 25% HF + 0.02% sodium ferrate, and the quartz sand is heated and dynamically pickled and purified in a high-purity quartz sand pickling and purification device, and the acid solution temperature is maintained at 80°C and kept warm for 3 hours. After the insulation time is completed, the acid solution is removed, and the material is washed with clean tap water until neutral, and then dehydrated for use.
[0103] 6. Put the quartz sand in step 5 into the composite acid solution composed of 20% HCl + 8% HF + 0.05% EDTA (mass percentage concentration) for dynamic pickling at a temperature of 80°C for 3 hours, and then remove the acid solution. Wash the quartz sand with clean tap water until it is neutral, then wash it with electronic grade pure water for at least three times and dehydrate it for later use.
[0104] 7. High temperature drying: The quartz sand in step 6 is sent to a high temperature drying device for drying at 950°C. The dried quartz sand is a high-purity quartz sand product with low hydroxyl and low alkali metal content.
[0105] Sampling and testing show that the sum of the oxide contents of Al, Fe, K, Na, Ca, Mg, Li, Co, Ni, Cr, Mn, Ti, P, B and Cu in the quartz sand product obtained in this embodiment is 18.6 ppm; among them, Al: 10.4 ppm, Fe: 0.5 ppm, and the five alkali metal and alkaline earth metal impurities of K, Na, Ca, Mg and Li are all less than 1.0 ppm; titanium: 1.3 ppm.
[0106] The hydroxyl content in the quartz glass rod prepared from this sand is 3 ppm.
[0107] Example 8
[0108] The same igneous vein quartz ore and purification process as in Example 7 were used, except that the composite acid solution used in step 6 had a composition of 20% HCl+8% HF+0.01% EDTA (mass percentage concentration).
[0109] The sum of the oxide contents of Al, Fe, K, Na, Ca, Mg, Li, Co, Ni, Cr, Mn, Ti, P, B and Cu in the obtained quartz sand product is 31 ppm; among them, Al: 15.5 ppm, Fe: 0.6 ppm, and the five alkali metal and alkaline earth metal impurities of K, Na, Ca, Mg and Li are all less than 1.0 ppm; titanium: 1.5 ppm.
[0110] The hydroxyl content in the quartz glass rod prepared using this sand as raw material is 3 ppm.
[0111] Example 9
[0112] The same igneous vein quartz ore and purification process as in Example 7 were used, except that the composite acid solution used in step 6 had a composition of 20% HCl+8% HF+0.1% EDTA (mass percentage concentration).
[0113] The sum of the oxide contents of Al, Fe, K, Na, Ca, Mg, Li, Co, Ni, Cr, Mn, Ti, P, B and Cu in the obtained quartz sand product is 21ppm; among them, Al: 14.0ppm, Fe: 0.5ppm, and the five alkali metal and alkaline earth metal impurities of K, Na, Ca, Mg and Li are all less than 1ppm; titanium: 1.4ppm.
[0114] The hydroxyl content in the quartz glass rod prepared using this sand as raw material is 3 ppm.
[0115] The above is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and changes can be made without departing from the principle of the present invention, and these improvements and changes are also regarded as the protection scope of the present invention.
Claims
1. A method for preparing low-hydroxyl, low-alkali metal high-purity quartz sand, characterized in that: The steps include: (1) Using igneous rock vein quartz as raw material, crushing the raw material to make sand, and obtaining raw quartz sand; (2) HF is used as pH adjuster and activator, and dodecylamine is used as collector to float the raw quartz sand; (3) Using a composite acid solution composed of HF and ferrate to perform oxidative acid washing and impurity removal on the raw quartz sand after flotation; (4) After the raw quartz sand is cleaned by oxidative pickling and mixed with carbon powder, it is calcined at 1100~1350℃ to remove gas-liquid inclusions in the quartz; (5) The raw quartz sand obtained in step (4) is pickled and impurities removed by using a composite acid solution composed of a halogen acid and a heavy metal complexing agent. After the pickling, the acid solution is removed, the sand is washed with water, and the sand is dried to obtain the high-purity quartz sand with low hydroxyl and low alkali metal content.
2. The method for preparing low-hydroxyl and low-alkali metal high-purity quartz sand according to claim 1, characterized in that: An iron removal step is also provided between step (1) and step (2), wherein the iron removal step adopts either electromagnetic separation or pickling or a combination of the two.
3. The method for preparing low-hydroxyl and low-alkali metal high-purity quartz sand according to claim 2, characterized in that: When pickling is used to remove iron, the acid solution is hydrochloric acid with a concentration of 28 wt%~30wt%, the pickling temperature is 80~85℃, and the pickling time is 3~4 hours.
4. The method for preparing low-hydroxyl and low-alkali metal high-purity quartz sand according to claim 1, characterized in that: The pH value range of flotation in step (2) is 2.0-2.5; the concentration of collector added is 500-1000 g / t; and the number of flotation times is 2-8 times.
5. The method for preparing low-hydroxyl and low-alkali metal high-purity quartz sand according to claim 1, characterized in that: The temperature of the oxidative pickling and impurity removal in step (3) is 80±5°C, and the time of the oxidative pickling and impurity removal is 2 to 4 hours; the temperature of the pickling and impurity removal in step (5) is 80±5°C, and the pickling time is 2 to 4 hours.
6. The method for preparing low-hydroxyl and low-alkali metal high-purity quartz sand according to claim 1, characterized in that: In step (3), the composite acid solution used for oxidative pickling and impurity removal has a HF mass fraction of 10% to 30% and a ferrate mass fraction of 0.001% to 0.1%.
7. The method for preparing low-hydroxyl and low-alkali metal high-purity quartz sand according to claim 1, characterized in that: In step (5), the mass fraction of the halogen acid in the composite acid solution used for pickling and impurity removal is 20% to 30%, and the mass fraction of the heavy metal complexing agent is 0.01% to 0.2%.
8. The method for preparing low-hydroxyl and low-alkali metal high-purity quartz sand according to claim 1, characterized in that: Step (4) is performed before step (3).
9. The method for preparing low-hydroxyl and low-alkali metal high-purity quartz sand according to claim 1, characterized in that: In step (4), the mass of the carbon powder is 0.8% to 3% of the mass of the raw material quartz sand.
10. The method for preparing low-hydroxyl and low-alkali metal high-purity quartz sand according to claim 1, characterized in that: The drying temperature in step (5) is 900-1000°C.
Citation Information
Patent Citations
High-purity quartz sand purifying and pickling device
CN102303870A
Purification method of high-purity quartz sand with SiO2 purity more than or equal to 99.99%
CN110127708A